Chemoreflex Control as the Cornerstone in Immersion Water Sports: Possible Role on Breath-Hold - Arce-Álvarez, Alexis; Salazar-Ardiles, Camila; Cornejo, Carlos; Paez, Valeria; Vásquez-Muñoz, Manuel; Stillner-Vilches, Katherine; Jara, Catherine R.; Ramirez-Campillo, Rodrigo; Izquierdo, Mikel; Andrade, David C. (Frontiers in Physiology, 2022)
Immersion water sports involve long-term apneas; therefore, athletes must physiologically adapt to maintain muscle oxygenation, despite not performing pulmonary ventilation. Breath-holding (i.e., apnea) is common in water sports, and it involves a decrease and increases in PaO2 and PaCO2, respectively, as the primary signals that trigger the end of apnea. The principal physiological O2 sensors are the carotid bodies, which are able to detect arterial gases and metabolic alterations before reaching the brain, which aids in adjusting the cardiorespiratory system. Moreover, the principal H+/CO2 sensor is the retrotrapezoid nucleus, which is located at the brainstem level; this mechanism contributes to detecting respiratory and metabolic acidosis. Although these sensors have been characterized in pathophysiological states, current evidence shows a possible role for these mechanisms as physiological sensors during voluntary apnea. Divers and swimmer athletes have been found to displayed longer apnea times than land sports athletes, as well as decreased peripheral O2 and central CO2 chemoreflex control. However, although chemosensitivity at rest could be decreased, we recently found marked sympathoexcitation during maximum voluntary apnea in young swimmers, which could activate the spleen (which is a reservoir organ for oxygenated blood). Therefore, it is possible that the chemoreflex, autonomic function, and storage/delivery oxygen organ(s) are linked to apnea in immersion water sports. In this review, we summarized the available evidence related to chemoreflex control in immersion water sports. Subsequently, we propose a possible physiological mechanistic model that could contribute to providing new avenues for understanding the respiratory physiology of water sports.